الذكاء الاصطناعي والتحول الرقمي واقتصاديات التعليم - Mustapha Ibrahim Shuaibu (Aqlamuna: Journal of Educational Studies, 2024)
يتطرق هذا البحث إلى تأثير الذكاء الاصطناعي والتحول الرقمي على اقتصاديات التعليم، مع التركيز على دور هذه التقنيات في تحسين جودة التعليم وزيادة الوصول إلى الفئات المهمشة. يحيل البحث إلى أن الابتكار التقني في قطاع التعليم يسهم في تحسين الكفاءة وتقليل التكاليف، مما يسهل تقديم خدمات تعليمية لأعداد أكبر من الطلاب، خاصة في المناطق النائية. كما أن الذكاء الاصطناعي يساعد في تخصيص التجارب التعليمية بما يتناسب مع احتياجات الطلاب، مما يعزز فعالية التعلم ويسهم في تحسين الأداء الأكاديمي. يتناول البحث أيضاً تحليل التكلفة والفائدة من تطبيق تكنولوجيا الذكاء الاصطناعي في التعليم، موضحًا أنه بالرغم من التحديات المرتبطة بتطبيق هذه التقنيات، مثل نقص المعرفة والموارد البشرية المؤهلة، إلا أن الفوائد المحتملة، مثل تحسين الأداء الأكاديمي وزيادة التفاعل بين الطلاب والمعلمين، تجعل هذه الاستثمارات ذات جدوى اقتصادية كبيرة. كما يعرض البحث تأثير التحولات الرقمية على سوق العمل، حيث يبرز الحاجة إلى مهارات رقمية متقدمة تتطلب تحديث المناهج التعليمية بما يتماشى مع تطورات سوق العمل. يستعرض البحث كذلك اتجاهات التمويل في تكنولوجيا التعليم، موضحًا أن التعاون بين المؤسسات المالية والتكنولوجية يعزز الابتكار في التعليم ويسهم في تحقيق الاستدامة المالية. يقدم البحث توصيات سياساتية تركز على تطوير استراتيجيات تعليمية مدعمة بالتكنولوجيا، مع ضرورة معالجة الفجوات الرقمية وتعزيز التدريب المستمر للمعلمين والطلاب. يؤكد البحث على أن تكامل الذكاء الاصطناعي مع السياسات التعليمية الفعالة يعد ركيزة أساسية لتحقيق التنمية المستدامة في مجال التعليم. This research examines the impact of artificial intelligence and digital transformation on the economics of education, focusing on the role of these technologies in improving the quality of education and increasing access to marginalized groups. The research suggests that technological innovation in the education sector enhances efficiency and reduces costs, making it easier to provide educational services to more students, especially in remote areas. AI also helps tailor learning experiences to students' needs, enhancing learning effectiveness and academic performance. The research also examines the cost and benefit of applying AI technology in education, explaining that despite the challenges associated with the application of these technologies, such as the lack of knowledge and qualified human resources, the potential benefits, such as improving academic performance and increasing interaction between students and teachers, make these investments very economically viable. The research also presents the impact of digital transformations on the labor market, highlighting the need for advanced digital skills that require updating educational curricula in line with labor market developments. The research also reviews funding trends in educational technology, explaining that cooperation between financial and technological institutions promotes innovation in education and contributes to achieving financial sustainability. The research provides policy recommendations focused on developing technology-enabled education strategies, addressing digital divides, and promoting ongoing training for teachers and students. Research confirms that the integration of artificial intelligence with effective educational policies is a key pillar for achieving sustainable development in the field of education.